2012
DOI: 10.1155/2012/436174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Selective Progesterone Receptor Modulator on Induction of Apoptosis in Uterine Fibroids In Vivo

Abstract: Aim. To determine if hormonal treatment induces apoptosis in uterine fibroids. Methods. Immunohistochemical examination of fibroid tissue, using avidin-biotin complex and cleaved caspase-3 antibody for detecting apoptosis, was performed in premenopausal women who underwent 12-week treatment with oral SPRM (6 patients with 5 mg and 5 patients with 10 mg of ulipristal acetate per day) or gonadoliberin agonist (GnRHa, 17 patients) and subsequent myomectomy or hysterectomy for symptomatic uterine fibroids. Ten pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 46 publications
2
25
0
4
Order By: Relevance
“…PCNA protein was increased after SPRM treatment, in contrast to several previous reports of decreased PCNA levels in cultured leiomyoma cells after treatment with SPRM [21]. However, similar to previous reports [22], caspase-3 protein was increased by SPRM treatment. Eventually, proliferation and apoptosis were also observed after in vivo SPRM, although fibroid volume was reduced by approximately 30%, indicating that SPRM may precipitate fibroid reduction through an apoptotic rather than anti-proliferative effect.…”
Section: Commentsupporting
confidence: 78%
“…PCNA protein was increased after SPRM treatment, in contrast to several previous reports of decreased PCNA levels in cultured leiomyoma cells after treatment with SPRM [21]. However, similar to previous reports [22], caspase-3 protein was increased by SPRM treatment. Eventually, proliferation and apoptosis were also observed after in vivo SPRM, although fibroid volume was reduced by approximately 30%, indicating that SPRM may precipitate fibroid reduction through an apoptotic rather than anti-proliferative effect.…”
Section: Commentsupporting
confidence: 78%
“…Ulipristal acetate, a selective P receptor (PR) modulator with pharmacokinetic properties supporting once daily dosing (13) potently modulates PR activity without suppressing E 2 to postmenopausal levels, and shows proapoptotic/antiproliferative effects on fibroid cells (13)(14)(15)(16)(17). Several short-term (3 months) randomized clinical studies showed that ulipristal acetate effectively controls bleeding and shrinks fibroids (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…UPA is a selective Progesterone receptor modulator (SPRM) that potently modulates P-receptor activity [ 23 ] with proapoptotic/ antiproliferative effects on fi broid cells [ 24 ] and with pharmacokinetic properties supporting once daily dosing [ 25 ]. Two short-term (3 months) randomized clinical trials showed that UPA effectively controls HMB and shrinks fi broids [ 26 , 27 ].…”
Section: Ulipristal Acetatementioning
confidence: 99%